2013
DOI: 10.1038/cddis.2013.285
|View full text |Cite
|
Sign up to set email alerts
|

Marchantin M: a novel inhibitor of proteasome induces autophagic cell death in prostate cancer cells

Abstract: We previously reported that marchantin M (Mar) is an active agent to induce apoptosis in human prostate cancer (PCa), but the molecular mechanisms of action remain largely unknown. Here, we demonstrate that Mar potently inhibited chymotrypsin-like and peptidyl-glutamyl peptide-hydrolyzing activities of 20S proteasome both in in vitro and intracellular systems and significantly induced the accumulation of polyubiquitinated proteins in PCa cells. The computational modeling analysis suggested that Mar non-covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
3
36
0
1
Order By: Relevance
“…Studies have shown that impairment of proteasomal activity can lead to increased autophagy (70,71), which would also explain the decreased amount of Ub-M-GFP accumulation in Fig. 5B, right panel.…”
Section: The Nkg2d Ligand-regulating Effect Of Ch 3 Seh and An Hdac Imentioning
confidence: 98%
“…Studies have shown that impairment of proteasomal activity can lead to increased autophagy (70,71), which would also explain the decreased amount of Ub-M-GFP accumulation in Fig. 5B, right panel.…”
Section: The Nkg2d Ligand-regulating Effect Of Ch 3 Seh and An Hdac Imentioning
confidence: 98%
“…Differently than in the thyroid cancer cells [78], both in SH-SY5Y cells and in the midbrain of the UPS-impaired mouse model of PD, treatment with lactacystin significantly increased the level of not only LC3-I/II but also Beclin-1 protein, and reduced the levels of p-mTOR and mTOR [85]. Moreover, Marchantin M, a novel proteasome inhibitor tested in prostate cancer cells, significantly induced expression of LC3-I and its further conversion to LC3-II [87].…”
Section: Effects Of Different Classes Of Proteasome Inhibitors On Autmentioning
confidence: 99%
“…Studies on Marchantin M-induced, PI3K/Vps34-dependent autophagy revealed that not the IRE1/JNK pathway but the PERK/eIF2a pathway seemed to be involved in autophagy induction by this proteasome inhibitor [87]. Although activation of the IRE1-mediated pathway of UPR was observed, a downstream effect of this activation was the increase in the spliced form of XBP-1 mRNA, however, the translated protein was found to be not involved in the autophagy induction [87]. In the same study, evaluation of ATF6-mediated pathway showed just a slight increase of ATF6 mRNA.…”
Section: Unfolded Protein Responsementioning
confidence: 99%
See 2 more Smart Citations